Microfinance and regional growth in Peru - Aguilar Andía, Giovanna (2013)
The objective of this study is to make a quantitative evaluation of the impact that the expansion of microcredit has had on the growth of economic activity in the Peruvian regions. Taking as a theoretical framework the theory developed to analyze the relationship between economic growth and financial development and with annual information for 24 regions of the country for the period 2001 - 2008, a panel data model is estimated with per capita GDP growth as a dependent variable; and the loans provided by various types of microfinance institutions, loans from commercial banks and other variables that affect economic growth as explanatory variables. The evidence found suggests that microfinancial expansion has a positive impact on the growth of economic activity in the regions, which is not the case for the expansion of banking intermediation. A comparative static exercise shows that if CMAC, CRAC and specialized bank loans come to reach10% of GDP in each region, the growth rate of GDP per capita would rise by at least 4 percentage points. In the regions with greatest poverty, this increase is much more striking and significant.